Darkness by design the hidden power in global capital markets - Mattli, Walter (Princeton University Press, 2019)
An exposé of fragmented trading platforms, poor governance, and exploitative practices in today's capital marketsCapital markets have undergone a dramatic transformation in the past two decades. Algorithmic high-speed supercomputing has replaced traditional floor trading and human market makers, while centralized exchanges that once ensured fairness and transparency have fragmented into a dizzying array of competing exchanges and trading platforms. Darkness by Design exposes the unseen perils of market fragmentation and "dark" markets, some of which are deliberately designed to enable the transfer of wealth from the weak to the powerful.Walter Mattli traces the fall of the traditional exchange model of the NYSE, the world's leading stock market in the twentieth century, showing how it has come to be supplanted by fragmented markets whose governance is frequently set up to allow unscrupulous operators to exploit conflicts of interest at the expense of an unsuspecting public. Market makers have few obligations, market surveillance is neglected or impossible, enforcement is ineffective, and new technologies are not necessarily used to improve oversight but to offer lucrative preferential market access to select clients in ways that are often hidden. Mattli argues that power politics is central in today's fragmented markets. He sheds critical light on how the redistribution of power and influence has created new winners and losers in capital markets and lays the groundwork for sensible reforms to combat shady trading schemes and reclaim these markets for the long-term benefit of everyone.Essential reading for anyone with money in the stock market, Darkness by Design challenges the conventional view of markets and reveals the troubling implications of unchecked market power for the health of the global economy and society as a whole.